Ritual Practices: An Emergentist Perspective - Bennett-Hunter, Guy (The expository times, 2017)
The theological use of the concept of emergence and of philosophical theories known as emergentism, has recently increased in popularity. After a brief introduction, the second section of this article argues that the most philosophically promising version of emergentism is one informed by classical and contemporary pragmatism. The third section describes in some detail the entanglement of facts and values that this form of emergentism implies. The final two sections apply pragmatistic emergentism theologically, with a focus on religious rituals and, in particular, the ritual washing of Eucharistic vessels. It concludes that pragmatistic emergentism, with its distinctive perspective on the entanglement of facts and values, can help to make philosophical sense of an otherwise unintelligible ritual practice.